Formation of positive ions in hydrocarbon containing dielectric barrier discharge plasmas. Issue 11 (1st December 2016) - Mihaila, Ilarion; Pohoata, Valentin; Jijie, Roxana; Nastuta, Andrei Vasile; Rusu, Ioana Alexandra; Topala, Ionut
Abstract: Low temperature atmospheric pressure plasma devices are suitable experimental solutions to generate transitory molecular environments with various applications. In this study we present experimental results regarding the plasma chemistry of dielectric barrier discharges (DBD) in helium - hydrogen (0.1%) - hydrocarbons (1.2%) mixtures. Four types of hydrocarbon gases were studied: methane ( CH 4 ), ethane ( C 2 H 6 ), propane ( C 3 H 8 ), and butane ( C 4 H 10 ). Discharge diagnosis and monitoring was assured by electrical measurements and optical emission spectroscopy. Molecular beam mass spectrometry is engaged to sample positive ions populations from two different plasma sources. Dissociation and generation of higher-chain and cyclic (aromatic) hydrocarbons were discussed as a function of feed gas and discharge geometry. We found a strong influence of these parameters on both molecular mass distribution and recombination processes in the plasma volume.